Sexing the citizen : morality and masculinity in France, 1870-1920 - Surkis, Judith (Cornell University Press, 2006)
"How did marriage come to be seen as the foundation and guarantee of social stability in Third Republic France? In Sexing the Citizen, Judith Surkis shows how masculine sexuality became central to the making of a republican social order. Marriage, Surkis argues, affirmed the citizen's masculinity, while also containing and controlling his desires. This ideal offered a specific response to the problems -- individualism, democratization, and rapid technological and social change -- associated with France's modernity